1980
DOI: 10.1111/j.1469-1809.1980.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

A cytogenetic study of 1000 spontaneous abortions

Abstract: Cytogenetic analysis of 1000 spontaneous abortions showed 463 to have an abnormal chromosome constitution. The proportion of chromosome abnormalities varied with the gestational age of the abortus and the type of tissue cultured but was not significantly different among the five racial groups represented in the study population. It was suggested that differences in the rate of chromosome abnormalities among cytogenetic studies of spontaneous abortions were the result of methodological differences in sample sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
293
2
18

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(345 citation statements)
references
References 15 publications
19
293
2
18
Order By: Relevance
“…The risk of chromosomal abnormalities in spontaneous pregnancy loss is approximately 50 % in the general population based upon original work in 1980 [6]. In couples undergoing assisted reproductive technologies (ART) the risk of spontaneous abortion and karyotypic abnormalities are less clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of chromosomal abnormalities in spontaneous pregnancy loss is approximately 50 % in the general population based upon original work in 1980 [6]. In couples undergoing assisted reproductive technologies (ART) the risk of spontaneous abortion and karyotypic abnormalities are less clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that approximately 50% of first-trimester SA is chromosomally abnormal. 6,8,10,30 Chromosome analysis is the current gold standard for detection of chromosome aberrations; however, approximately 20% of POC samples fail to yield a chromosome result due to culture failure, often attributable to microbial contamination or nonviable tissue.…”
Section: Overviewmentioning
confidence: 99%
“…In addition, it has been demonstrated that the increasing aneuploidy rates in human oocytes and embryos are observed relative to advanced maternal age [5]. Women over 38 years old had poor IVF outcomes, especially in women over 40 years old [6].…”
mentioning
confidence: 99%